CONVICÇÕES DE SAÚDE EM PACIENTES COM CÂNCER - Pires, Eliana Ferrante (2008)
This search proposes to describe convictions health factors present in patients with cancer, which can interfere with the process of accession to treatment. For both were used testemonials of six patients in the form of directed interviews, involved in a program of service helth at a university of Greater Sao Paulo. The content of the interviews was analyzed according to a model of conviction health, which advocates that the patients will have greater opportunities to adhere to the following five treatments convictions basics health, namely: susceptibility, severity, benefits, barriers, own efficiency. A extension of this model was proposed by another study that adds two more categories to the existing: impact on diagnosis and expectations for the future.(AU)